A targeted siRNA‐loaded PDL1‐exosome and functional evaluation against lung cancer. Issue 11 (11th May 2022) - Lin, Xianbin; Lin, Liangan; Wu, Jingyang; Jiang, Wentan; Wu, Jiayun; Yang, Jianshen; Chen, Chun
Abstract: Background: As an endocytic nanosicle involved in intercellular communication, an exosome can efficiently deliver drugs from one cell to another and deliver therapeutic short interfering RNA (siRNA) to target cells. This is conducive to gene therapy for cancers. In this study, an exosome was used as the siRNA‐loaded substrate to prepare a targeted siRNA‐loaded PD‐L1 exosome and evaluate its function against lung cancer. Methods: The optimal preparation process and binding ratio of the targeted nanovesicle/siRNA complex was determined by detecting the particle size, potential, and other physical parameters in combination with cell binding and uptake capacity of exosome complexes. The biological cell behavior of targeted exosome nanosicles was evaluated through cytotoxicity, apoptosis, and the cell uptake capacity. Results: A targeted exosome nanovesicle capable of loading siRNA and characterized with low toxicity, high loading rate, and the ability to be used for targeted tumor cell gene therapy was constructed. Conclusion: The PD‐L1 targeting exosome can be used as an efficient siRNA delivery carrier, which is an efficient and safe nanocarrier for tumor targeted gene therapy. Abstract : A targeted exosome nanovesicle capable of loading siRNA and characterized with low toxicity, high loading rate and the ability of targeted gene therapy for tumor cells was constructed to effectively inhibit lung cancer cells.